2014
DOI: 10.1186/1752-1947-8-340
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis associated with invasive malignant thymoma: two case reports and a review of the literature

Abstract: IntroductionApproximately ten to fifteen percent of patients with myasthenia gravis are found to have a thymoma, and twenty to twenty-five percent of patients with thymoma have myasthenia gravis. Thymomatous myasthenia gravis tends to have a difficult clinical course and poor prognosis.Case presentationWe report two cases (one patient of Asian ethnicity and the other of Caucasian ethnicity) of atypical presentations of myasthenia gravis associated with invasive malignant thymoma. Both patients were diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Our patient showed drastic symptomatic improvement after undergoing fi ve rounds of plasmapheresis. Moderate MG symptom improvement has been reported with removal of thymic carcinoma metastases to the pleura (8). Unfortunately, our patient was not a surgical candidate due to multiple extrathoracic metastases.…”
Section: Malignant Thymoma With Metastasis Associated With Paraneoplamentioning
confidence: 70%
See 1 more Smart Citation
“…Our patient showed drastic symptomatic improvement after undergoing fi ve rounds of plasmapheresis. Moderate MG symptom improvement has been reported with removal of thymic carcinoma metastases to the pleura (8). Unfortunately, our patient was not a surgical candidate due to multiple extrathoracic metastases.…”
Section: Malignant Thymoma With Metastasis Associated With Paraneoplamentioning
confidence: 70%
“…A small biopsy cannot adequately demonstrate the mixed histology that can be present. Metastasis from thymic tumors is most commonly seen in lymph nodes, liver, and soft tissue/skeletal muscles, with other sites including bone, brain, and abdominal wall (8)(9)(10)(11).…”
Section: Malignant Thymoma With Metastasis Associated With Paraneoplamentioning
confidence: 99%
“…23 Our high mortality rate is comparable with that found in a study of 19 Other recent reports of MG with invasive thymoma described good outcome in 2 patients. 21 The patients who died in our series had uncontrolled respiratory failure. In a study of 8 patients with MG who died with thymoma, in 6 the cause of death was exacerbation of MG. 20 As already mentioned, in patients with thymoma with MG, the outcome is related to the ability to achieve clinical remission of MG. 17 All our patients were AChR Ab positive.…”
Section: Discussionmentioning
confidence: 97%
“…One study found that the presence of invasive thymoma with MG is associated with worse prognosis than invasive thymoma alone, 18 which indicates that the prognosis is influenced by the additional issues associated with MG, and some other small case series report outcomes. [19][20][21] We present the clinical characteristics of 6 subjects with MG and invasive thymoma, to demonstrate the clinical course and the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10%–20% of patients with MG are found to have a thymoma . In the United States, the incidence of thymoma is 0.15 per 100,000 person‐years, and it is highest among Asians, Pacific Islanders, and African Americans …”
mentioning
confidence: 99%